The Effectiveness of Premarital Counseling on Understanding the Sakinah, Mawaddah, and Rahmah Family Concept at the Bululawang Office of Religious Affairs - Robbani, Muhammad Asrorur; Hidayat, Sachrawi; Madyan, Syamsu; Muhibbin, Moh.; Ardiansyah, Muhammad (ISTIFHAM, 2026)
This study aims to analyze the effectiveness of the premarital counseling program organized by the Office of Religious Affairs (Kantor Urusan Agama/KUA) of Bululawang District, Malang Regency, in enhancing prospective brides’ and grooms’ knowledge of the concepts of sakinah, mawaddah, and rahmah in family life. The high divorce rate in Indonesia—reaching 480,618 cases in 2021, with 110 cases recorded in Bululawang District alone in 2022—constitutes the underlying urgency of this research. This study employs a descriptive, qualitative approach using field research methods. Data were collected through participant observation, in-depth interviews, and documentation. Informants included the head of the KUA, marriage counselors, program facilitators, and ten pairs of prospective brides and grooms. The findings indicate that: (1) the premarital counseling program at the KUA of Bululawang has been implemented in accordance with the Regulation of the Director General of Islamic Community Guidance (Bimas Islam) Number 379 of 2018, encompassing six core modules delivered using andragogical methods; (2) supporting factors include the availability of instructional modules, the capacity of certified facilitators, and adequate facilities and infrastructure, while inhibiting factors comprise budget constraints, the absence of mandatory participation regulations, and suboptimal participant engagement; (3) overall, the premarital counseling program has proven effective in enhancing both the knowledge and psychological readiness of prospective couples, with the average readiness score reaching 74.65%. This study recommends strengthening regulations to mandate participation in premarital counseling programs and increasing budget allocations for the KUA.